Resistive switching in ceramic multiferroic Bi 0.9Ca 0.1FeO 3 - Rubi, Diego (2011)
We report resistive switching effects in polycrystalline samples of the multiferroic Bi 0.9Ca 0.1FeO 3 with silver electrodes. Mössbauer spectroscopy shows that upon Ca-doping the Fe remains in a 3 valence state, suggesting charge compensation through the creation of large amounts of oxygen vacancies. Electrical characterization shows that the oxide/metal resistance can be switched between high and low resistance states by applying voltage pulses. This process was shown to be forming free and a strong relaxation after switching was found. We rationalize our results by considering oxygen vacancies migration to and from the metal-oxide interface, resulting in variations of the Schottky potential barrier height that modulate the interface resistance.